Role of IWMI in water management for the betterment of agriculture in rural India - Sikka, Alok K (Indian Farming, 2018)
In conclusion, area specific solutions to irrigation and water management, both technological and policy related, can address the context and area specific migration issues. This calls for prioritizing and mainstreaming regionally differentiated interventions through development programmes and policies with matching investments in agriculture and rural development. It is relevant to note that the Government of India has undertaken Flagship programme on providing water access to each farm through Prime Minister Krishi Sinchaayee Yojana and its effective implementation could help in reversing the migration and improving agricultural productivity. The IWMI is committed to working closely with its host organization, The ICAR as well as Ministry of Water Resources, River Development and Ganga Rejuvenation, Government of India and other relevant partners.